Research Relevance in the Trump 2.0 Era: Navigating Policy, Trade, and Business Scholarship - Kamal Upadhyaya; Subroto Roy (American Business Review)
As editors of the American Business Review (ABR), we write this editorial at a moment of global inflection. ABR has prioritized research that matters—not only to academic scholars, but to business practitioners, students, and policy observers. The new policy directions under the Trump 2.0 administration offer a reconfigured environment, where global trade, education, immigration, and enterprise are undergoing rapid recalibration. These changes call for rigorous academic engagement, not ideological entrenchment.